Simulation of a rl load fed by a matrix converter with Matlab/simulink - Günd?du, Ahmet; Altun, Hüseyin (My University, 2009)
In this study, 3-phase matrix converter which is feeding an RL load and using Venturini's control algorithm has been mathematically analyzed. By considering this mathematical analysis the matrix converter has been modeled in Matlab/Simulink and simulation results have been obtained for different output frequencies. The simulation results were obtained for two different switching frequencies, 2 kHz and 5 kHz and by using Venturini's modulation algorithm which uses q<=0.5 voltage transfer ratio. Venturini's control algorithm used in this study can be realized by using more simple and cheaper controllers. In addition, from the simulation results obtained for different output voltage and frequency values, it has been demonstrated that magnitude of the harmonic content except the fundamental component is very low for input current and output voltage of the matrix converter.
Rl yükünü besleyen matri?s konverteri?n matlab/simulink i?le benzeti?mi?
Keywords: Matrix converter; Venturini modulation algorithm